CHALLENGES IN LESSON PLANNING AND POSSIBLE SOLUTIONS - Sojida Yoqubjanova (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article explores one of the major issues identified during teaching practice—ineffective lesson planning—and examines its impact on both teaching quality and student learning outcomes. The research is grounded in a combination of classroom observations, reflective questions, a review of relevant academic literature, and survey data collected from teachers as well as students. These methods made it possible to gain a comprehensive understanding of how insufficient planning can affect lesson structure, time management, and student engagement. Furthermore, a demo lesson was designed and conducted to test practical strategies aimed at improving lesson planning. The results of this experimental approach revealed that well-organized lessons contribute significantly to better classroom management, clearer instruction, and more active student participation. In contrast, poorly planned lessons often lead to confusion, time loss, and reduced effectiveness of the teaching process. The findings underline the importance of systematic lesson preparation, including setting clear objectives, selecting appropriate materials, and allocating time efficiently. Overall, the study demonstrates that improving lesson planning skills is essential for teachers who seek to enhance their professional performance and achieve more successful educational outcomes.